Pengaruh Internal Corporate Governance Mechanisms dan Eksternal Audit Quality terhadap Audit Report Lag di Indonesia - Irvandika Rheza Dhevanda; Agus Purwanto (Diponegoro Journal of Accounting, 2026)
This study aims to examine the effect of corporate governance characteristics and other related factors on audit report lag in non-financial companies listed on the Indonesia Stock Exchange (IDX) and included in the LQ45 Index during the 2022–2024 period. Audit report lag refers to the period between a company's fiscal year-end and the issuance date of the independent auditor’s report. Timely submission of audited financial statements is an important aspect in maintaining the relevance and quality of financial information for stakeholders. The independent variables employed in this study include audit committee size, audit committee independence, audit committee expertise, audit committee diligence, board of commissioners size, board of commissioners independence, board of commissioners diligence, external auditor reputation, firm size, profitability, gender diversity of the board of commissioners, and the Covid-19 pandemic. The sample was selected using a purposive sampling method. Of the initial 135 observations, 24 observations were excluded because they did not meet the research criteria, resulting in a final sample of 111 observations. Hypothesis testing was conducted using multiple linear regression analysis. The results indicate that audit committee independence, board of commissioners size, and external auditor reputation have a negative and significant effect on audit report lag. These findings suggest that higher audit committee independence, larger board size, and higher external auditor reputation are associated with shorter audit report lag. Meanwhile, audit committee size, audit committee expertise, audit committee diligence, board of commissioners independence, and board of commissioners diligence do not have a significant effect on audit report lag. The findings imply that the effectiveness of corporate oversight in accelerating the audit completion process is more strongly influenced by audit committee independence, the supervisory capacity of the board of commissioners, and external auditor quality than by the number of members, expertise, or meeting frequency of corporate governance bodies. This study is expected to contribute to the literature on audit report lag and provide insights for companies, auditors, and regulators in improving corporate governance effectiveness and the timeliness of financial reporting.